Highly fluorescent anthracene derivative as a non-fullerene acceptor in OSCs with small non-radiative energy loss of 0.22 eV and high PCEs of over 13%. Issue 17 (11th April 2019) - Yao, Chao; Liu, Bin; Zhu, Yanan; Hong, Ling; Miao, Jingsheng; Hou, Jianhui; He, Feng; Meng, Hong
Abstract : Herein, we designed and synthesized a highly fluorescent non-fullerene acceptor (ANT-4F) based on an anthracene (ANT) core. Abstract : Herein, we designed and synthesized a highly fluorescent non-fullerene acceptor (ANT-4F) based on an anthracene (ANT) core. OSCs based on ANT-4F/PBDB-TF exhibited a significantly decreased V loss, non-rad of 0.22 V (calculated from high EQEEL = 1.7 × 10 −4 ). Simultaneously, high charge-transfer state energy ( E CT = 1.54 eV) was obtained. Compared with OSCs based on IT-4F/PBDB-TF, a reduced V loss, non-rad and higher E CT concurrently contributed to an increased V oc of 0.93 V. Consequently, despite the lower J sc of 19.0 mA cm −2, an overall high PCE of 13.1% can be obtained. This work exemplified the great potential for highly fluorescent NFSAs in decreasing V loss, non-rad and improving PCEs.